EXPLORING STUDENTS’ CONTROL OVER LEARNING MANAGEMENT: A TECHNICAL PERSPECTIVE OF AUTONOMY IN LANGUAGE LEARNING - Priyatno Ardi (University of Muhammadiyah Purwokerto, 2014)
Autonomy in language learning suggests that students control their own learning (Benson, 2001). Students’ control over their own learning consists of three aspects, namely controls over learning management, cognitive process and learning content. This paper aims at exploring stu-dents’ control over learning management while working on project-based English language learn-ing, namely the collaborative audio-journal project. It is argued that project-based language learn-ing provides a principled and practicable route toward autonomy (Thomas, 1991, cited in Benson, 2001: 21).In this regards,students themselves plan, monitor, solve problems, and evaluate the pro-ject accomplishment without much intervention from the teacher. A qualitative method was employed in this study. Two instruments were used to obtain the data, namely reflection sheet and interview. The results obtained from the study revealed that students employed four major controls over learning management, including planning, problem solving, monitoring, and evaluating. The planning included time and quality, creativity, and strategy. The students also encountered the constraints, such as time management, language proficiency, and laziness, which entailed problem solving strategies. The monitoring included rereading, re-listening, and comparing. Lastly, the students conducted self-evaluation on the process and the product. Key words: learner autonomy, project-based language learning, andcontrol over learning man-agement.